2014
DOI: 10.1080/13573322.2013.860894
|View full text |Cite
|
Sign up to set email alerts
|

Sport and physical activity in the lives of looked-after children: a ‘hidden group’ in research, policy and practice

Abstract: Looked-after children are arguably one of the most disadvantaged groups in society and constitute a 'hidden group' in relation to sport and physical activity research, policy and practice. Research on looked-after children has explored the views of care-givers, practitioners and policy-makers who have often been asked to speak for children on their behalf. Through the use of the mosaic approach and innovative participatory methods, including peer interviewing, the purpose of this paper was to provide an insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
3
34
0
2
Order By: Relevance
“…The glimpses the film provides into "the girls" (as they preferred to be referred to) everyday participation are examples of what Hart (2009, p. 4) would call the "cracks between adult-organised events" (facilitated activities). Our research supports arguments that participation in social, cultural and leisure activities improve, at least, the self-reported well-being of young people growing up in care (see, for instance, Gilligan, 2007;Hollingworth, 2012;Quarmby, 2014;Säfvenbom & Samdahl, 2000). However, little is known about the complexity and diversity of activities and everyday interests young people are offered, where and whom they participate with, and the values that influence their everyday choices.…”
Section: Participation and Young People In Caresupporting
confidence: 57%
See 1 more Smart Citation
“…The glimpses the film provides into "the girls" (as they preferred to be referred to) everyday participation are examples of what Hart (2009, p. 4) would call the "cracks between adult-organised events" (facilitated activities). Our research supports arguments that participation in social, cultural and leisure activities improve, at least, the self-reported well-being of young people growing up in care (see, for instance, Gilligan, 2007;Hollingworth, 2012;Quarmby, 2014;Säfvenbom & Samdahl, 2000). However, little is known about the complexity and diversity of activities and everyday interests young people are offered, where and whom they participate with, and the values that influence their everyday choices.…”
Section: Participation and Young People In Caresupporting
confidence: 57%
“…Research shows that participation in "positive activities" plays a significant role in improving or ensuring the well-being, personal development and future outcomes of "looked-after" young people (for instance, Gilligan, 2007;Hollingworth, 2012;Quarmby, 2014;Säfvenbom & Samdahl, 2000). As a result of this, the participation of young people in care in a range of extra-curricular activities is legislated as a responsibility of the "corporate parent".…”
Section: Participation and Young People In Carementioning
confidence: 99%
“…Bailey (2005) found that there were positive associations between reduced anti-social behaviour and participation in PE and sport, whilst Sandford, Duncombe, and Armour (2008) and Armour and Sandford (2013) argued that physical activity could also be linked to reduced incidence of anti-social behaviour and disaffection with schooling in youth. Quarmby's (2014) investigation found that sports club partnerships with vulnerable 'looked after' children were perceived to be helpful in overcoming institutional constraints that disrupted their engagement with schooling and sports participation. Armour and Duncombe's (2012) evaluation of United Kingdom school-based athlete role-model intervention programs revealed a central premise that interaction with a highly successful athlete could positively impact upon a child's life -particularly those children not gaining the most benefit from schooling.…”
Section: Were the Players Role Models?mentioning
confidence: 98%
“…Jachyra, 2016;Lyngstad, Hagen & Aune, 2016). Yet one 'group', care-experienced young people, remain 'hidden' within the prevailing literature (Quarmby, 2014). Care-experienced young people include anyone who is currently, or has been at any stage of their life, in care.…”
Section: Introductionmentioning
confidence: 99%